Public health expenditures and health outcomes: New evidence from Ghana - Micheal Kofi Boachie; K. Ramu; Tatjana P\~olajeva (Economies, 2018)
The effect of government spending on population's health has received attention over the past decades. This study re-examines the link between government health expenditures and health outcomes to establish whether government intervention in the health sector improves outcomes. The study uses annual data for the period 1980-2014 on Ghana. The ordinary least squares (OLS) and the two-stage least squares (2SLS) estimators are employed for analyses; the regression estimates are then used to conduct cost-effectiveness analysis. The results show that, aside from income, public health expenditure contributed to the improvements in health outcomes in Ghana for the period. We find that, overall, increasing public health expenditure by 10% averts 0.102-4.4 infant and under-five deaths in every 1000 live births while increasing life expectancy at birth by 0.77-47 days in a year. For each health outcome indicator, the effect of income dominates that of public spending. The cost per childhood mortality averted ranged from US0.20 to US16, whereas the cost per extra life year gained ranged from US7 to US593.33 (2005 US) during the period. Although the health effect of income outweighs that of public health spending, high (and rising) income inequality makes government intervention necessary. In this respect, development policy should consider raising health sector investment inter alia to improve health conditions.
Keywords: H51; I10; I18; I31; 330; public health expenditures; health outcomes; cost-effectiveness; Ghana